Runners Adapt Different Lower-Limb Movement Patterns With Respect to Different Speeds and Downhill Slopes - Sundström, David; Kurz, Markus; Björklund, Glenn (Frontiers in Sports and Active Living, 2021)
The aim of the study was to investigate the influence of slope and speed on lower-limb kinematics and energy cost of running. Six well-trained runners (VO2max 72 ± 6 mL·kg-1·min-1) were recruited for the study and performed: 1) VO2max and energy-cost tests and 2) an experimental running protocol at two speeds, 12 km·h-1 and a speed corresponding to 80% of VO2max (V80, 15.8 ± 1.3 km·h-1) on three different slopes (0°, -5° and -10°) totalling six 5-min workload conditions. The workload conditions were randomly ordered and performed continuously. The tests lasted 30 min in total. All testing was performed on a large treadmill (3×5 m) that offered control over both speed and slope. Three-dimensional kinematic data of the right lower limb were captured during the experimental running protocol using eight infrared cameras with a sampling frequency of 150 Hz. Running kinematics were calculated using a lower body model and inverse kinematics approach. The generic model contained three, one and two degrees of freedom at the hip, knee and ankle joints, respectively. Oxygen uptake was measured throughout the experimental protocol. Maximum hip extension and flexion during the stance phase increased due to higher speed (p<0.01 and p<0.01, respectively). Knee extension at touchdown and maximal knee flexion in the stance phase both increased on steeper downhill slopes (both p<0.05). Ground contact time decreased as speed increased (p<0.01) but was unaffected by slope (p=0.73). Runners modified their hip movement pattern in the sagittal plane in response to changes in speed, whereas they altered their knee movement pattern during the touchdown and stance phases in response to changes in slope. While energy cost of running was unaffected by speed alone (p = 0.379), a shift in energy cost was observed for different speeds as the downhill gradient increased (p < 0.001). Energy cost was lower at V80 than 12 km·h-1 on a -5° slope but worse on a -10° slope. This indicates that higher speeds are more efficient on moderate downhill slopes (-5°), while lower speeds are more efficient on steeper downhill slopes (-10°).